Isotopic characterization of the metabasites and amphibolites of the Acungui and Setuva Groups of the Ribeira Belt - Farias de Oliveira, Marcos Aurélio [UNESP]; Maniesi, Vanderlei; Teixeira, Wilson; Daitx, Elias Carneiro [UNESP] (My University, 2002)
Pb, Rb, Sr, Sm and Nd isotope analyses were carried out on amphibolitic rocks from Campo Largo (PR), Rio Branco do Sul (PR) and Adrianópolis (PR) and for the metabasite from Adrianópolis and Apiai (SP), all belonging to the Açungui and Setuva Groups, southern portion of the Ribeira Belt. These occurrences were chosen because each exhibits geochemical data indicative of a mantle source, having different signatures. Geochronologic determinations are available only for the Apiai metagabbro with Neoproterozoic ages of 617 ± 4 Ma (U/Pb in zircon) and 839 ± 85 Ma (Rb/Sr, whole rock). Age determinations by Sm/Nd mineral isochron using whole rock, plagioclase and pyroxene yield values of 885 ± 53 Ma for the Apiai metagabbro and 820 ± 84 Ma for the Adrianópolis metabasite. These results agree within error with the Rb/Sr isochron of 839 ± 85 Ma may possibly be interpreted as the time of extraction of the magma from the mantle, as suggested by positive εNd(850) values (+2,76) from an Adrianópolis sample. An εNd values versus 87Sr/86Sr diagram shows that each studied occurrence plots in a different position, following approximately the mantle array trend, the most primitive being the metabasite of Adrian-acopolis, near the MORB field, and the most enriched being the amphibolite from the same region, near the enriched mantle and or crustal contamination field. The distinct difference in isotopic signatures between the amphibolite and metabasite suggests derivation from different mantle sources, as supported by available geochemical data. Nevertheless, some of the samples show isotopic evidence of the action of metamorphism, crustal contamination and weathering.
Keywords: Crustal contamination; Geochronology; Isotopes; Matabasite and amphibolite; Ribeira Belt; amphibolite; crustal contamination; geochemistry; geochronology; isotopic composition; metabasite; Proterozoic; Brazil